Formation of Socio-Cultural Competence Through the Use of Case Study Technology in Teaching a Foreign Language (Journal of Educational Sciences, 2025)
In this article, the “case study” technique is used to solve an issue and explore ways to motivate students more in the process of developing their socio-cultural competence in a foreign language. The influence of case technology on students is examined, as well as its function in the development of socio-cultural components of foreign language instruction. This method’s overall content and functioning were shown as part of the scientific investigation.  We discovered that students learn communication, curiosity, creativity, and practical skills with the use of Case Technologies. The case technique boosts students' motivation to learn, according to the study.  Along with these abilities, language learners can also assimilate information fast and effortlessly and speak freely in groups about what they have learned.  Students were questioned both before and after the research regarding the case method's efficacy, their motivation to learn about cultural traits, and their level of sociocultural competency. The findings were then analysed based on the students’ perspectives. Teachers were provided methodological advice to boost student motivation based on a research course that examined students' interest to learn the cultural features of other nation.Key words: “case-study” method, socio-cultural competence, motivation, English language, innovation system, technology, technique, motivation.